Paciente de sexo masculino de 44 años de edad que presenta tumor retroperitoneal - Triviño Armache, Sheyla Isabel (2020)
Retroperitoneal tumors are tumors that are difficult to detect very early, their detection is late, for their slow growth causing symptoms when they reach large dimensions such as back pain, nausea, vomiting, epigastric discomfort, weight loss, these tumors can occur solidly or cystic which have a benign characteristic of 15% and the malignant in 85%, the diagnostic for these tumors are imaging tests such as abdominal ultrasound. The case presented below it was valued and was diagnosed nutritionally to a 44-year-old male patient who has retroperitoneal tumor, which indicates that for 1 month he presents discomfort with pain at the lower limb level, and that approximately For 3 months he lost weight significantly, in parallel he presents diabetes mellitus and hypertension. Anthropometric evaluation it was performed revealing a body mass index of 15.06 kg / m2, which according to the cut-off points of the World Organization of the Health, the patient presents a nutritional status of Severe Malnutrition, also the Nutritional Biochemistry reported hematological alterations linked with nutritional deficit, a feeding plan was designed to palliate the nutritional deficit and dietary therapeutic treatment to its base pathologies.